2014
DOI: 10.1371/journal.pone.0104638
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Chondrocytes in the Rabbit Growth Plate Can Proliferate and Differentiate into Osteogenic Cells when Capillary Invasion Is Interposed by a Membrane Filter

Abstract: The fate of hypertrophic chondrocytes during endochondral ossification remains controversial. It has long been thought that the calcified cartilage is invaded by blood vessels and that new bone is deposited on the surface of the eroded cartilage by newly arrived cells. The present study was designed to determine whether hypertrophic chondrocytes were destined to die or could survive to participate in new bone formation. In a rabbit experiment, a membrane filter with a pore size of 1 µm was inserted in the midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Taken in conjunction with the unexpected finding that some HCs in the MCC (Fig. 1) and growth plate (Enishi et al 2014;Zhou et al 2014) undergo cell division, this hints at a surprising functional plasticity for HCs. While the environmental cues and regulators of these changes are not now understood, the possibilities are tantalizing.…”
Section: Discussionmentioning
confidence: 71%
“…Taken in conjunction with the unexpected finding that some HCs in the MCC (Fig. 1) and growth plate (Enishi et al 2014;Zhou et al 2014) undergo cell division, this hints at a surprising functional plasticity for HCs. While the environmental cues and regulators of these changes are not now understood, the possibilities are tantalizing.…”
Section: Discussionmentioning
confidence: 71%
“…Another speculation regarding the changes in the growth plate of the 2.3   kb Col 1a1-Cre;Fam20C flox/flox mice in which Fam20C was not ablated in chondrocytes may be related to potential interacting relationships between the chondrocytes and endochondral bone formation. Several recent studies have indicated that in the process of endochondral bone formation of the long bones, chondrocytes may directly differentiate into osteogenic cells 2225 . If a certain population of chondrocytes in the growth plate are transformed into osteoblasts that are responsible for new bone formation, then it is tempting to speculate that when the endochondral bone formation is defective, the osteogenic cells may send feedback signals via an unknown signaling pathway to the chondrocytes in the growth plate and may affect the normal development of the cartilaginous tissues, leading to the growth plate defects in the long bones of the 2.3   kb Col 1a1-Cre;Fam20C flox/flox mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, degradation of the mineralized cartilage matrix is accompanied by the release of high local concentrations of signaling molecules, peptides, ions and glycans that can regulate cell fate; indeed, phosphate was shown to induce apoptosis of cultured chick chondrocytes (Magne et al 2003;Mansfield et al 2003). When cartilage resorption was disturbed by inserting a permeable membrane filter that separated ª 2015 Japanese Society of Developmental Biologists the HZ from the chondro-osseous junction in rabbit, the HCs underwent cell division and differentiate to become osteogenic cells (Enishi et al 2014), resembling the chick studies mentioned above. Hence, the fate of HCs is likely context-dependent.…”
Section: Programmed To Die?mentioning
confidence: 99%
“…Evidence from the literature indicates the ª 2015 Japanese Society of Developmental Biologists decision is probably circumstantial, and may depend on both intrinsic and extrinsic factors. Enishi et al suggest that diffusible osteogenic factors from the primary spongiosa may be important for promoting the proliferation and osteoblastic differentiation of HCs in their membrane interposition model (Enishi et al 2014), since interposition by impermeable membrane resulted only in an expansion of HZ (Salter & Harris 1963). It is already known that HCs can secrete VEGF and RANKL to attract endothelial cells and chondroclasts, respectively (Zelzer et al 2001;Xiong et al 2011), so it is also likely that stimulatory signals could be sent to the HCs from the primary spongiosa.…”
Section: Modern Lineage Tracing Provides Evidence For Pro-lifementioning
confidence: 99%